2022
DOI: 10.1080/13576275.2022.2107424
|View full text |Cite
|
Sign up to set email alerts
|

Patient and family caregiver perspectives of Advance Care Planning: qualitative findings from the ACTION cluster randomised controlled trial of an adapted respecting choices intervention

Abstract: Advance Care Planning (ACP) is widely regarded as a component of good end-of-life care. However, findings from a qualitative international study of patient and family caregiver attitudes and preferences regarding ACP highlight participants' ambivalence towards confronting the future and the factors underlying their motivation to accept or defer anticipatory planning. They show how ACP impacts on, and can be determined by, relationships between patients and their family caregivers. Although some patients may we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Furthermore, our results showed that the relatives found the conversation valuable in regard to talking about other important matters relating to EOL. This finding is supported by the study by Pollock et al (2022), who found that ACP conversations could provide an opportunity for a dialogue between the patients and their relatives and help them make decisions for the future.…”
Section: Discussionmentioning
confidence: 64%
“…Furthermore, our results showed that the relatives found the conversation valuable in regard to talking about other important matters relating to EOL. This finding is supported by the study by Pollock et al (2022), who found that ACP conversations could provide an opportunity for a dialogue between the patients and their relatives and help them make decisions for the future.…”
Section: Discussionmentioning
confidence: 64%
“…This was also found in other studies, in which patients or family carers did not want to distress or alarm each other. [46][47][48] Interestingly, our study showed the persons with amyotrophic lateral sclerosis and family carers also tried to protect themselves from burdensome emotions by not talking about the future which often manifested itself in living by a "day-by-day attitude," prioritizing current care management and quality of life over longterm planning. It was observed that some family carers experienced increasing anxiety over time, particularly when unable to share their concerns with others, highlighting the importance of involving them in advance care planning conversations.…”
Section: Interpretation Of the Main Findingsmentioning
confidence: 86%
“…This was also found in other studies, in which patients or family carers did not want to distress or alarm each other. 46 48…”
Section: Discussionmentioning
confidence: 99%
“…The ACTION qualitative study explored patient and family experience of receiving the ACTION RC ACP intervention and their perspectives on ACP (Pollock et al, 2022 ). This present paper reports on how taking part in the ACTION RC ACP intervention may support hope as one of the secondary objectives of the ACTION qualitative study.…”
Section: Methodsmentioning
confidence: 99%